Pomen socialnih omrežij za revitalizacijo nekdanjih industrijskih mestnih območij - primer nekdanje Tobačne tovarne v Ljubljani - Uršič, Matjaž (Družboslovne razprave, 2019)
Analysis of social networks in areas undergoing intense urban transformations are becoming an ever more important topic in spatial planning. The growing attention given to social networks is due to the rise of problems and conflicts stemming from disregard of the "soft", i.e. social, components in the local environment. The problem of stakeholders' participation and empowerment in spatial planning is, in fact, one of ignoring or not recognising the importance of the social networks that exist between actors in space. The article analyses the roles and meanings of social networks with respect to the development of certain types of socio-economic activities in former industrial areas. Using data collected from semi-structured interviews in the area of former Tobacco Factory in Ljubljana, it analyses the types, intensity and expansion of social networks
Keywords: City planning; Družbena omrežja; former industrial areas; nekdanja industrijska območja; participation; participiranje; Revitalizacija mest; Revitalization of cities; Social networks; social spatial nodes; socialna prostorska vozlišča; Tobacco Factory Ljubljana; Tobačna tovarna Ljubljana; Urbanizem